LINC00673 Represses CDKN2C and Promotes the Proliferation of Esophageal Squamous Cell Carcinoma Cells by EZH2-Mediated H3K27 Trimethylation - Zhou, Menghan; Mao, Yuhang; Yu, Shenling; Li, Yiping; Yin, Rong; Zhang, Qin; Lu, Tianyu; Sun, Rui; Lin, Shaofeng; Qian, Yanyan; Xu, Ying; Fan, Hong (Frontiers in Oncology, 2020)
Long noncoding RNAs (lncRNAs), some of the most abundant epigenetic regulators, play an important role in esophageal squamous cell carcinoma (ESCC). In the current study, the functions and mechanisms of the lncRNA LINC00673 were investigated. Expression levels of LINC00673 and its potential target genes were assessed by quantitative real-time polymerase chain reaction (q-PCR) in ESCC surgical specimens and ESCC cell lines. RNA fluorescence in situ hybridization (RNA FISH) was employed to detect the subcellular location and level of LINC00673 in ESCC samples from patients with different survival times. LINC00673 function in ESCC carcinogenesis was also evaluated in vivo and in vitro. Cell cycle synchronization was performed using serum withdrawal; the cell cycle was monitored by fluorescence analysis, and cellular DNA was detected by flow cytometry. The molecular mechanisms underlying LINC00673 were explored via western blotting, chromatin immunoprecipitation (ChIP) and ChIP-PCR. Upregulated LINC00673 was associated with poor prognosis in ESCC patients and promoted the proliferation of ESCC cells both in vitro and in vivo. Compared to the control group, depletion of LINC00673 in ESCC cells arrested the cell cycle, at least, at the G1/S checkpoint. Knockdown of LINC00673 significantly enhanced posttranscriptional expression of CDKN2C, and histone 3 lysine 27 trimethylation (H3K27me3) was enriched at the promoter region of CDKN2C. After inhibiting EZH2, CDKN2C expression levels were increased. The present findings are the first to reveal that LINC00673 represses CDKN2C expression and promotes ESCC cell proliferation by elevating EZH2-mediated H3K27me3 levels. These data suggest that LINC00673 regulates the cell cycle in ESCC and LINC00673 is a promising target for clinical therapy.